Association between impacted mandibular third molar and occurrence of mandibular angle fracture: A radiological study - Karpal Singh Sohal; Jeremiah Robert Moshy; Sira Stanslaus Owibingire; Elison N M. Simon (Wolters Kluwer Medknow Publications, 2019)
Background: Presence of an impacted mandibular third molar contributes to the weakness of the angle region of the mandible and increases the risk of its fracture. The influence of the presence of impacted mandibular third molars on the occurrence of angle fractures is, however, imprecisely estimated despite boundless research on this subject. Aim: To determine the influence of impacted third molars on the incidence of mandibular angle fractures. Materials and Methods: This was a retrospective study of panoramic radiographs (orthopantomogram [OPG]) that were taken at the Radiology Unit of the Department of Oral and Maxillofacial Surgery, Muhimbili University of Health and Allied Sciences, for 2 years. The collected data included presence of fracture of mandibular angle, presence/absence of impacted lower third molar, and classification of impacted tooth. Data were analyzed using Statistical Package for the Social Sciences software Version 22. A significant level of P < 0.05 was considered. Results: Two-hundred and sixty-eight OPGs were studied. Fracture of the mandibular angle was in about a quarter (25.4%) of them. According to Winter's classification, 44.3% of the impacted teeth had mesioangular inclination, and by Pell and Gregory's classification, 72.2% and 60.8% of the impacted teeth were in Class II and Position A, respectively. In more than half (59.7%) of the fractures of mandibular angle, there was the presence of impacted mandibular third molars. The odds of sustaining fracture to the angle of mandible was about nine times higher in the presence of an impacted lower third molar (odds ratio 8.7, 95% confidence interval: 4.71-16.11). Conclusion: The presence of impacted third molars increases the risk of mandibular angle fracture; however, the classification of impacted tooth by Winter's or Pell and Gregory's methods had no significant role in occurrence of the mandibular angle fracture.